Consolidated bioprocessing of starchy substrates into ethanol by industrial Saccharomyces cerevisiae strains secreting fungal amylases. Issue 9 (14th July 2015) - Favaro, Lorenzo; Viktor, Marko J.; Rose, Shaunita H.; Viljoen‐Bloom, Marinda; van Zyl, Willem H.; Basaglia, Marina; Cagnin, Lorenzo; Casella, Sergio
Abstract The development of a yeast strain that converts raw starch to ethanol in one step (called Consolidated Bioprocessing, CBP) could significantly reduce the commercial costs of starch‐based bioethanol. An efficient amylolytic Saccharomyces cerevisiae strain suitable for industrial bioethanol production was developed in this study. Codon‐optimized variants of the Thermomyces lanuginosus glucoamylase (TLG1) and Saccharomycopsis fibuligera α‐amylase (SFA1) genes were δ‐integrated into two S. cerevisiae yeast with promising industrial traits, i.e., strains M2n and MEL2. The recombinant M2n[TLG1‐SFA1] and MEL2[TLG1‐SFA1] yeast displayed high enzyme activities on soluble and raw starch (up to 8118 and 4461 nkat/g dry cell weight, respectively) and produced about 64 g/L ethanol from 200 g/L raw corn starch in a bioreactor, corresponding to 55% of the theoretical maximum ethanol yield (g of ethanol/g of available glucose equivalent). Their starch‐to‐ethanol conversion efficiencies were even higher on natural sorghum and triticale substrates (62 and 73% of the theoretical yield, respectively). This is the first report of direct ethanol production from natural starchy substrates (without any pre‐treatment or commercial enzyme addition) using industrial yeast strains co‐secreting both a glucoamylase and α‐amylase. Biotechnol. Bioeng. 2015;112: 1751–1760. © 2015 Wiley Periodicals, Inc.